(untitled) (Biological Sciences - PJSIR, 1998)
The complex dielectric constant and the related properties of petroleum and their mixtures have been analyzed using Chelsea Dielectric Interface System, a microprocessor based Digital Dielectric Spectrometer. Frequency response curves have been drawn for the frequency range 0.lHz-1MHz, at 303.5 "K, The real and imaginary part of dielectric constant E’ and E", and dissipation loss factor ’tan 8’ have been plotted as a function of frequency. From the study of dielectric data, a general formalism is obtained for the permitivity of mixtures as a function of measurable parameters of its mixing components.